2011
DOI: 10.1128/jvi.02032-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Adenovirus Type 5 Induces Cell Lysis through Autophagy and Autophagy-Triggered Caspase Activity

Abstract: Oncolytic adenoviruses, such as Delta-24-RGD, are promising therapies for patients with brain tumor. Clinical trials have shown that the potency of these cancer-selective adenoviruses should be increased to optimize therapeutic efficacy. One potential strategy is to increase the efficiency of adenovirus-induced cell lysis, a mechanism that has not been clearly described. In this study, for the first time, we report that autophagy plays a role in adenovirus-induced cell lysis. At the late stage after adenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 39 publications
4
110
0
Order By: Relevance
“…In conclusion, the present findings, together with those of recent studies in T cell clonal expansion (15), proteasome inhibition (29), and oncolytic adenovirus (28), indicate that the autophagosomal membrane may serve as a platform for iDISC formation, which activates caspase-8 and the caspase cascade, leading to autophagy-dependent apoptosis. As many anticancer therapies induce both apoptosis and autophagy, establishment of an autophagy-dependent mechanism of caspase activation reveals a novel strategy to enhance therapeutic efficacy in tumor cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In conclusion, the present findings, together with those of recent studies in T cell clonal expansion (15), proteasome inhibition (29), and oncolytic adenovirus (28), indicate that the autophagosomal membrane may serve as a platform for iDISC formation, which activates caspase-8 and the caspase cascade, leading to autophagy-dependent apoptosis. As many anticancer therapies induce both apoptosis and autophagy, establishment of an autophagy-dependent mechanism of caspase activation reveals a novel strategy to enhance therapeutic efficacy in tumor cells.…”
Section: Discussionmentioning
confidence: 78%
“…To support this concept, forced membrane localization and self-association of caspase-8 has been shown to dramatically promote apoptosis (43). Furthermore, it has recently been suggested that caspase-8 is recruited to the Atg12-Atg5 complex through FADD and that autophagic machinery is required for activation of caspase-8 (6,15,28). In this study, we show that the caspase-8⅐FADD complex associates with Atg5 on Atg16-and LC3-positive structures, indicating that the autophagosomal membrane serves as a platform for this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been reported that Ad5 induces cell lysis through autophagy and that viruses may also use autophagy-related vacuoles as a means for new progeny to exit the infected cell (27). In addition, the combination of an adenovirus with an autophagy inducer correlates positively with virus replication, improving the efficacy of Ad-mediated oncolysis.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Autophagic induced cell death and induction of apoptosis are well-characterized results of Ad-Δ24 infection giving the erratum for combination treatments. [26] ANTITUMOR IMMUNE RESPONSE Another important aspect of oncolytic virotherapy is the induction of augmented antitumor immune response. [27,28] Ad-Δ24-RGD has been shown to induce antiglioma immunity and to enhance the presentation of tumor-associated antigens to immune cells.…”
Section: Combination Treatmentsmentioning
confidence: 99%